Three-dimensional human bile duct formation from chemically induced human liver progenitor cells - Li, Peilin; Miyamoto, Daisuke; Huang, Yu; Adachi, Tomohiko; Hidaka, Masaaki; Hara, Takanobu; Soyama, Akihiko; Matsushima, Hajime; Imamura, Hajime; Kanetaka, Kengo; Gu, Weili; Eguchi, Susumu (Frontiers in Bioengineering and Biotechnology, 2023)
The intrahepatic bile ducts (BDs) play an important role in the modification and transport of bile, and the integration between the BD and hepatocytes is the basis of the liver function. However, the lack of a source of cholangiocytes limits in vitro research.The aim of the present study was to establish three-dimensional BDs combined with human mature hepatocytes (hMHs) in vitro using chemically induced human liver progenitor cells (hCLiPs) derived from hMHs.Methods: In this study, we formed functional BDs from hCLiPs using hepatocyte growth factor and extracellular matrix. BDs expressed the typical biliary markers CK-7, GGT1, CFTR and EpCAM and were able to transport the bile-like substance rhodamine 123 into the lumen. The established three-dimensional BDs were cocultured with hMHs. These cells were able to bind to the BDs, and the bile acid analog CLF was transported from the culture medium through the hMHs and accumulated in the lumen of the BDs. The BDs generated from the hCLiPs showed a BD function and a physiological system (e.g., the transport of bile within the liver) when they were connected to the hMHs.We present a novel in vitro three-dimensional BD combined with hMHs for study, drug screening and the therapeutic modulation of the cholangiocyte function.